Mental Health, Loneliness, and Social Support Among Undergraduate Students: A Multinational Study in Asia. (May 2023) - Backhaus, Insa; Fitri, Mustika; Esfahani, Mahdi; Ngo, Huyen Thi; Lin, Li-jung; Yamanaka, Akira; Alhumaid, Majed M.; Qin, Ling; Khan, Azizuddin; Fadzullah, Nur 'Ashikin; Khoo, Selina
In this study, we aimed to investigate the prevalence of poor mental health and its association with loneliness and social support among 3531 undergraduate students in nine Asian countries. Mental health was assessed using the Self-Reporting Questionnaire, which was developed by the World Health Organization. Across the entire sample, we detected that nearly half of the students reported poor mental health according to the Self-Reporting Questionnaire and nearly one out of seven students felt lonely. While feeling lonely increased the odds of experiencing poor mental health (odds ratio [OR]), moderate (OR: 0.35) and strong social support (OR: 0.18) decreases the odds of experiencing poor mental health. The high prevalence of poor mental health calls for further in-depth investigations and implementation of mental health support interventions.